GOOD CORPORATE GOVERNANCE DAN PERLINDUNGAN KONSUMEN: STUDI KASUS: PENYALAHGUNAAN DATA KARTU TELEPON BEKAS - Angeline Thalita (Politeknik Ubaya, 2021)
Abstract This study aimed to investigate the extent of the application of the principles of Good Corporate Governance (GCG) and protection of personal data from the point of view of consumers in telecommunications service companies. The case study analyzed the misuse of used telephone card data in a telecommunications service company PT. Z. The empirical judicial method was used in this study. This legal research was carried out by examining documents (document studies), using 2 (two) approaches, the statute approach and the conceptual approach. Primary data were collected through surveys and interviews to prove the findings in the first stage. The results of the study, on the legal aspects showed that the legal protection for consumers as users of telecommunications services has not been fully implemented by PT. Z according to Law Number 8 of 1999 concerning Consumer Protection and Law Number 36 of 1999 concerning Telecommunications. Consumer perceptions indicate that PT. Z has not implemented GCG principles properly. Consumer responses to aspects of consumer personal data protection related to the above cases are also not good and tend to be detrimental to consumers. This research showed that the application of GCG principles is not optimal and has an impact on weak aspects of consumer protection. For the implementation of GCG in the future, PT. Z should have good intentions in running its business and provide correct, complete and clear information related to the products it trades, both spoken and written. Keywords : Good corporate governance, consumer protection, personal data protection, telecommunication service